(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In our country, everything is paid to the development of professional sports. The success of athletes in high-level competitions is an important component of the country’s international prestige. In this regard, the situation regarding the importance of the health of athletes for their achievement of high sports results has acquired special relevance [4; 17; 19]. Sports genetics is still at the beginning of the path, but at the same time it opens up many prospects for the development of medical and biological support for sports. The use of the genetic characteristics of the organism will lead humanity to new records, because now not only persistence, regular training, willpower and motivation of an athlete are important, but also his “Olympic” heredity. A detailed study of these genes is necessary for the correct organization of the training process, for predicting the capabilities of athletes. According to modern concepts of functional genomics, it is believed that individual differences in the degree of development of certain physical and mental qualities, as well as in the susceptibility to certain diseases of athletes, are largely due to DNA polymorphisms (variable regions in the DNA sequence). The FABP2 gene produces a protein that binds fatty acids in the digestive system, and thus directly regulates the absorption of fats in the epithelial cells of the small intestine (Baier, Sacchettini et al. 1995). Studies have shown that in the presence of the risk allele, the binding of fatty acids from food occurs to a greater extent and, the presence of the risk allele is directly associated with an increased body mass index, body fat, abdominal adipose tissue size and overweight (Baier, Sacchettini et al. 1995).